2015
DOI: 10.1111/head.12717
|View full text |Cite
|
Sign up to set email alerts
|

A Motion Simulator Ride Associated With Headache and Subdural Hematoma: First Case Report

Abstract: We report the first case report of symptomatic bilateral subdural hematomas (SDH) associated with riding a centrifugal motion simulator ride. A previously healthy 55-year-old male developed new onset daily headaches 1 week after going on the ride that were due to symptomatic bilateral SDH requiring operative intervention with a full recovery. There was no history of other trauma or other systemic or intracranial abnormality to account for the development of the SDH. We review the headaches and other clinical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Rigid body and finite element simulations provide a promising starting point to explore mechanisms for roller coaster induced subdural hematomas. 6,[8][9][10] Our rigid body simulations estimate roller coaster brain surface displacement on the order of 2.0-4.0mm, which may lead to stretching of the bridging veins between the brain and skull. 41 Although the rigid body model does not represent the bridging veins as individual substructures, we can estimate the maximum stretch within the sagittal plane: If bridging veins were oriented along the anterior-posterior direction and had an average length of 6.0 mm, they would experience stretches up to 1.67, which is close to or even beyond the critical bridging vein failure stretch of 1.50.…”
Section: Brain Deformation During Roller Coaster Rides Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Rigid body and finite element simulations provide a promising starting point to explore mechanisms for roller coaster induced subdural hematomas. 6,[8][9][10] Our rigid body simulations estimate roller coaster brain surface displacement on the order of 2.0-4.0mm, which may lead to stretching of the bridging veins between the brain and skull. 41 Although the rigid body model does not represent the bridging veins as individual substructures, we can estimate the maximum stretch within the sagittal plane: If bridging veins were oriented along the anterior-posterior direction and had an average length of 6.0 mm, they would experience stretches up to 1.67, which is close to or even beyond the critical bridging vein failure stretch of 1.50.…”
Section: Brain Deformation During Roller Coaster Rides Discussionmentioning
confidence: 93%
“…1 The accelerations experienced on roller coaster rides contribute to their thrilling nature; however, the effect of these accelerations on the brain is largely unknown. Previously, there have been several case studies reporting serious brain injuries attributed to roller coasters, [1][2][3] including seven cases of subdural hematoma, [4][5][6][7][8][9][10] two cases of subarachnoid hemorrhage, 11,12 and multiple cases of concussion. 1,13,14 These types of brain injuries have been extensively studied and are thought to be mostly caused by excessive mechanical deformations of the bridging veins causing subdural hematoma, 15 of aneurysms causing subarachnoid hemorrhage, 12,16 and of the parenchymal brain tissue itself causing concussion.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying pathophysiology is still not clearly understood; however, the anatomical nature of the bridging veins makes them more susceptible to rupture, as they lack the presence of any supporting reinforcement from the arachnoid in addition to their structural lack of elastic or muscular layers. [ 11 ] Furthermore, Yamashima and Friede’s study showed that subarachnoid veins share a uniform wall diameter of 50–200 um in addition to the fact that they obtain a dense reinforcement from the arachnoid trabecular cells; in contrast to the bridging veins, as they have different wall diameters and lack the volume of support from the arachnoid trabecular cells, and this makes them more prone to tearing and rupture. [ 14 ] In the light of these anatomic characteristics of the bridging veins with no apparent reason to explain their rupture and bleeding, such as brain atrophy, intracranial hypotension, or other previously mentioned reasons, we believe that the underlying cause of such presentation was a sudden rise in the pressure of the venous system, which led to veins rupture.…”
Section: Discussionmentioning
confidence: 99%
“…However, acceleration and deceleration forces on the head without direct head trauma can cause subdural hematomas, for example after roller-coaster rides, 6 so it might be expected that whiplash could cause trauma to the brain parenchyma as well. Similarly, many injuries to the head may also cause injury to the upper cervical spine.…”
Section: Head Trauma Versus Neck Traumamentioning
confidence: 99%